PHYSICOCHEMICAL PROPERTIES AND NUTRITION OF MORINGA OLEIFERA LAM. LEAF EXTRACT: A PRELIMINARY STUDY ON PREPARATION PHYTOSOMES AS HERBAL SUPPLEMENT FOR CHILDREN - WARDANA, MUTIA SARI; JUFRI, MAHDI; MUN’IM, ABDUL (International Journal of Applied Pharmaceutics, 2022)
Objective: The study aimed to evaluate the physicochemical properties and nutrition of Moringa leaf extract. In addition, the preliminary study for the preparation of Moringa leaf extract-loaded phytosomes for a supplement. Methods: Extraction of Moringa leaf made using microwave-assisted extraction, followed by evaluation of proximate analysis (water, total ash, acid-insoluble of ash contents, and residual n-hexane), phytochemical screening, and nutrition such as crude protein, amino acids, and minerals (iron, zinc, and calcium). The phytosomes were prepared by the anti-solvent precipitation method and assessed for the morphology, particle size, zeta potential, polydispersity index (PDI), entrapment efficiency (EE), and Fourier-transform infrared spectra. Results: The nutrition contents of crude protein, iron, zinc, and calcium were 19.61±0.07%, 3.47±0.00 mg/100g, 5.46±0.05 mg/100g, and 747.40±4.89 mg/100g, respectively. The amino acids with the highest concentrations were glutamic acid, phenylalanine, aspartic acid, alanine, and arginine in the extract. The best preparation using sonication 10 min by morphology was a spherical included particle size, PDI, zeta potential, and EE of arginine was 87.16±1.73 nm, 0.22±0.04, −23.07±0.76 mV, and 108.94±0.52%, respectively. Conclusion: These preliminary results provide evidence of the nutritional benefit of Moringa leaf extract-loaded phytosomes as a promising supplement to prevent stunting in children.